MANAJEMEN PRAKTIK KERJA INDUSTRI - Agus Numan Faizal; Burhanuddin Burhanuddin; Sultoni Sultoni (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2018)
Abstract: The purpose of this research to described the program planning school relations and the wider community in the practice of industrial work, the implementation of the, evaluation, obstacles and a solution .This study adopted qualitative approaches to a draft a case study .The result of this research is that the planning, the implementation of the, evaluation, obstacles and a solution the program school relations and the wider community in the practice of industrial work. Keywords: management of public relation, public relation, industrial work practices Abstrak: Tujuan penelitian ini untuk mendeskripsikan perencanaan program hubungan sekolah dan masyarakat dalam praktek kerja industri, pelaksanaan, evaluasi, kendala dan solusi. Penelitian ini menggunakan  pendekatan  kualitatif dengan rancangan studi kasus. Hasil penelitian ini adalah perencanaan, pelaksanaan, evaluasi, kendala dan solusi program hubungan sekolah dan masyarakat dalam praktek kerja industri. Kata Kunci: manajemen humas, humas, prakerin